If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 = 5(3g + 4) Reorder the terms: -25 = 5(4 + 3g) -25 = (4 * 5 + 3g * 5) -25 = (20 + 15g) Solving -25 = 20 + 15g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-15g' to each side of the equation. -25 + -15g = 20 + 15g + -15g Combine like terms: 15g + -15g = 0 -25 + -15g = 20 + 0 -25 + -15g = 20 Add '25' to each side of the equation. -25 + 25 + -15g = 20 + 25 Combine like terms: -25 + 25 = 0 0 + -15g = 20 + 25 -15g = 20 + 25 Combine like terms: 20 + 25 = 45 -15g = 45 Divide each side by '-15'. g = -3 Simplifying g = -3
| (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) | | 9x^4-19x^2-2=0 | | -3+x=6n+22 | | -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) | | -30x+12(x-1)=24x+2 | | 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= | | 3h=-18 |